Porous Epoxy: Effect of Mixing Sequences (ELH versus EHL) Using Toluene as Extraction Medium via Ultrasonic Technique - Siti Noorkhartina Ishak; Pei Leng Teh; Uy Lan Du Ngoc; Cheow Keat Yeoh (International Journal of Polymer Science)
Porous epoxy was fabricated using natural rubber latex (NRL) as the void template. In this study, two mixing sequences were selected: epoxy, hardener, and then latex (EHL) and epoxy, latex, and then hardener (ELH). The extraction process was carried out to extract the latex particles from the cured epoxy sample using toluene as extraction medium with ultrasonic technique for 1 hour. The formation of porous structure in epoxy system is dependent essentially on the amount of latex removed from the epoxy matrix. As expected, the density results showed lower values in the porous epoxy in ELH mixing sequences. More porous structure in epoxy was obtained which was proven by the increasing in porosity % which has led to lowering of the value in dielectric constant which is preferred for electronic packaging application. However, it also caused a decrease in flexural strength and modulus.